Effect Of Leaching Agents On Polyurethane Composite Scaffolds Containing Bioactive Glass - Lee, Angie (Universiti Sains Malaysia, 2017)
Eight samples of porous polyurethane composite scaffolds containing 45S5 bioactive glass were fabricated by salt-particle leaching method. Each sample contains 80% polyurethane and 20% 45S5 bioactive glass. Two different leaching agents, namely NaCl and NaHCO3 were used to create the porous structure of scaffolds. The ratio between NaCl and NaHCO3 were varied, with NaCl:NaHCO3 percentage being 100:0, 95:5, 90:10, 85:15, 80:20, 75:25, 70:30 and 0:100. The porous scaffolds were characterized based on its pore morphology as well as its thermal and mechanical properties. Bonding properties of scaffold samples were studied using Fourier Transform Infrared Spectroscopy (FTIR), whereas its pore morphology were studied using Scanning Electron Microscopy (SEM). Porous scaffolds fabricated exhibits pores of which their sizes range from tens of microns to hundreds, which are suitable for bone tissue engineering. Thermal behaviour of samples were investigated using Thermogravimetric Analysis (TGA). Result shows that the percentage of residues remained in the scaffold (at 700°C) increases with increasing amount of NaHCO3. Mechanical properties of the produced scaffolds were studied by though compression test. Compressive modulus of the fabricated scaffolds ranges from 0.11 to 2.15 MPa. Besides that, the total porosity existing in the scaffold was studied as well. A minimum porosity of 70% porosity is usually required for biomedical applications, whereby in this study, majority of the samples fabricated has sufficient porosity to be used for bone tissue engineering.